Maternal anxiety during universal newborn hearing screening at Hospital Universiti Sains Malaysia - Kamaruddin, Noor Rafidah (Universiti Sains Malaysia, 2009)
The purpose of this study was to investigate the maternal anxiety during Universal Newborn Hearing Screening (UNHS) at Hospital Universiti Sains Malaysia (HUSM). A sample of 50 mothers who had given birth at HUSM was surveyed using a set of questionnaire. The instruments were based upon demographic profile, knowledge about hearing screening and Beck Anxiety Inventory (BAI). BAI is a set of questionnaire used to assess the level of maternal anxiety. The data was coded and analyzed using Wilcoxon signed Rank Test of SPSS version 11.5. The findings indicated that majority of the mothers were having mild anxiety during the first screening and before they undergone the second screening. The result also showed that there was significant difference of maternal anxiety level between the first screenings and before the second screening. There was also significant difference in the level of maternal anxiety between mothers whose babies failed the first screening and passed the second screening. Even though both results showed that there was a significant reduction in the level of maternal anxiety, but some of them are still in anxiety state. Therefore, actions need to be taken to improve the failure rate in UNHS.